Training in Musculoskeletal Radiology in Europe: Philosophy, Challenges, and Practical Implementation - Eustace, Stephen J. (Seminars in Musculoskeletal Radiology, 2018)
This article provides an overview of the philosophy, mechanisms, and difficulties involved in the establishment of integrated training programs in medicine, radiology, and specifically musculoskeletal radiology across the European Union.
Keywords: Europe; musculoskeletal radiology; training